ANALYSIS OF THE TRANSLATION OF EVERYDAY REALITIES IN A.P. CHEKHOV’S STORY “VANKA” - Shiguo, Шань; Saparbayeva, Н.Б. (Journal of Oriental Studies, 2024)
In this article, the authors examine the features of translating realities in A. P. Chekhov’s fictional story “Vanka” into Chinese. The analysis showed that the translator must not only master all the necessary translation techniques and strategies, but also understand the character, culture and specific characteristics of this people. To study this study, the method of comparative analysis, generalization and the method of system analysis was used. As a result of the study, it was proven that in translating the story “Vanka” the authors used the method of transliteration, replacement of words, omission of words and the method of descriptive translation. The materials of the article can be used in teaching disciplines related to the theory and practice of translation. Keywords: everyday life, native language, Russian culture, method of system analysis, literary translation.